Stakeholders’ Opinions on the Development of a Master Program in Nursing Science, Faculty of Nursing, Princess of Naradhiwas University - Thaweeporn, Thaweeporn; Sangmanee, Rossukon; Siriphan, Siriphan; Tongnuang, Patcharawadee; Puangkaew, Danita (Princess of Naradhiwas University Journal, 2021)
This study aimed (1) to study the current situation, trend and educational requirements, (2) to analyze the feasibility of organizing and (3) to present the educational management of a master program in nursing science at the faculty of nursing, Princess of Naradhiwas University. 174 registered nurses and 91 of fourth year nursing students were selected by purposive sampling. The questionnaires were used as a research instrument which its index of item objective congruence was 1.0. The semi-structure interviews were conducted to collect data from 30 stakeholders including users of graduates and alumni of the faculty of nursing. Descriptive statistics including frequency, percentage, mean, and standard deviation, and content analysis were used for data analysis. According to the survey, the results showed that 53 registered nurses (42.74 percent) and 59 fourth-year nursing students (67.05 percent) have further requirements for pursuing a master’s degree in nursing science. The interested departments were mostly in adult and elderly nursing (35.8 percent) and elderly nursing (17.0 percent), and 60.4 percent of target participants prefer to register for weekend class. It was also found that 36 fourth-year nursing students (61.0 percent) can study while they do full-time job on weekdays. From the content analysis, it showed that the guidelines for the educational management was to develop graduates to be knowledgeable and able to see the cause of problems and be able to solve them, to build leadership in nursing, to develop graduates to obtain skills especially in research and innovation including understanding the context of a multicultural society in the three southern border provinces The master’s degree in nursing science is significant and is needed in this region. Suggestions for teaching and learning models should be cooperated between educational institutions to ensure efficient operation and academic excellence.